The Use of Short Tandem Repeat Analysis for Cell Line Authentication - M. D. Khorolsky; I. S. Semenova; E. V. Melnikova; Yu. V. Olefir (Биопрепараты: Профилактика, диагностика, лечение, 2019)
Short tandem repeat analysis (STR) is a well-established international method of authentication and genetic stability testing of cell lines (CLs). Therefore, the development and introduction of this method into routine practice of cell banks and cell culture collections is a pressing concern. In addition, the expansion of the field of cell-line based biomedical cell products (BСPs) necessitates the implementation of STR as a tool of identification testing during quality control. The State Pharmacopoeia of the Russian Federation does not require mandatory use of STR for cell line identification, while other countries have been using this method for cell line quality control for about a decade. The use of identified CLs in medical practice will ensure the efficacy and safety of BCPs. The aim of the study was to assess the possibility of using STR analysis for authentication and genetic stability testing of CLs using U937, WISH, WIL2-S, NK-92, and Jurkat Clone E6-1 CLs as examples. Materials and methods: the following human CLs were used in the study: U937 (ECACC), WISH (ATCC), WIL2S (ATCC), NK-92 (ATCC), and Jurkat Clone E6-1 (ATCC). The CL allelic profiles were determined by STR using the COrDIS Plus kit (Gordiz, Russia). The electrophoretic separation was performed using a Genetic Analyzer 3500 Series instrument. The data provided on the websites of the European Collection of Authenticated Cell Cultures and American Type Culture Collection were used to compare the CL profiles. Results: the AuthentiFiler PCR Amplification Kit (Thermo Fisher Scientific, USA) and the GenePrint 10 System (Promega Corporation, USA) intended for CL authentication by STR were compared with the characteristics of the COrDIS plus kit (Gordiz, Russia). The results of the comparison demonstrated that the COrDIS plus kit includes all the loci found in the foreign kits, as well as the loci recommended by the International Cell Line Authentication Committee. The U-937, WIL2S, and NK-92 CLs demonstrated genetic identity with the reference profiles available on the websites of the international collections. The Jurkat Clone E6-1 CL was found to be genetically instable due to the loss of the amelogenin gene. Conclusions: it was demonstrated by the examples of U937, WISH, WIL2-S, NK-92, and Jurkat Clone E6-1 CLs that STR and the COrDIS plus kit could be used for authentication and genetic stability testing. The obtained results suggest the feasibility of using the COrDIS plus kit for the analysis of CLs used in BCPs, for BCP quality control, and biomedical research.